KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Reza Septian Nugraha (University of Merdeka Malang, 2017)
The purpose of this study was to determine how big of a role Organizational Commitment as a mediation influence training and work discipline to employee performance at DPPKA Malang. The samples are 205 respondents to the sampling method using proportional random sampling method. The approach in this study is a quantitative approach that is supported by the survey, is explanatory. Testing hypotheses in this research using path analysis. The results showed that the training and work discipline can improve employee performance DPPKA Malang, training and discipline can enhance organizational commitment to DPPKA Malang, and organizational commitment has a role as mediation influence training and ork discipline to employee performance at DPPKA Malang. The findings empirically indicated that in order to increase the commitment and performance of employees, the Department of Finance and Asset Management Revenue (DPPKA) Malang regency need to pay attention to the factors that can influence organizational commitment and performance of employees. Recommendations relating to the results of this research in improving organizational commitment and employee performance, it is recommended leader that has the authority to control and more attention, and to conduct periodic performance evaluationsDOI : https://doi.org/10.26905/jbm.v4i1.1712